The Truth and Reconciliation Commission and the Law of Prior Consultation: Obstacles and Opportunities for Democratization and Political Participation in Peru - Sarmiento Barletti, J.P.; Seedhouse, L. (SAGE Publications, 2019)
A study informed by long-term fieldwork with Amazonian and Andean indigenous peoples examines their experiences of Peru’s Truth and Reconciliation Commission and Law of Prior Consultation. It engages with these efforts, which sought to address injustice by creating a new pact between the state and its indigenous citizens, their various failures, and the unintended opportunities that they have created for the political participation of indigenous peoples and their representatives.Un estudio basado en el trabajo de campo a largo plazo con los pueblos indígenas amazónicas y andinos examine sus experiencias de la Comisión de Verdad y Reconciliación y la Ley de Consulta Previa de Perú, que buscaba abordar la injusticia creando un nuevo pacto entre el estado y sus ciudadanos indígenas. Aborda sus diversos fracasos y las oportunidades no previstas que han creado para la participación políticas de los pueblos indígenas y sus representantes.